2012
DOI: 10.1016/j.pedneo.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Streptococcal Pharyngitis Score in Southern Taiwan

Abstract: Pediatric streptococcal pharyngitis in Southern Taiwan is uncommon. Diagnosis of GAS pharyngitis based on the McIsaac sore throat score is unreliable among pediatric patients with febrile pharyngitis in Southern Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
2
6
2
2
Order By: Relevance
“…Several studies have been published aiming to elucidate the clinical picture accuracy for the etiological diagnosis of APT in children, with variable results. 7,8,[12][13][14][15] Rimoin et al 16 demonstrated the existence of significant variation in the clinical presentation of APT in four different countries, suggesting it is inadequate to extrapolate conclusions about the clinical picture accuracy from one region to another. Therefore, the importance of the present study is emphasized, conducted in a country where RF and its complications are a major public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published aiming to elucidate the clinical picture accuracy for the etiological diagnosis of APT in children, with variable results. 7,8,[12][13][14][15] Rimoin et al 16 demonstrated the existence of significant variation in the clinical presentation of APT in four different countries, suggesting it is inadequate to extrapolate conclusions about the clinical picture accuracy from one region to another. Therefore, the importance of the present study is emphasized, conducted in a country where RF and its complications are a major public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with 11% reported in Turkey 16 ; 12% in Brazil 17 and 9.7% among healthy school children in Ethiopia. 18 But, it was much higher than the prevalence of 2.8%, 4.1% and 7.9%, Taiwan 19 and Indonesia. 20 respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical characteristics statistically associated with the presence of GAS vary among studies: 7 , 8 , 12 - 15 palatal petechiae; anterior cervical adenopathy; oropharyngeal exudate; sore throat; tonsillar hypertrophy; scarlet fever-like rash, fever >38°C; muscle pain; bad breath; oral ulcers; gastrointestinal symptoms; contact with patients with APT by GAS; age 5 to 12 years; and oropharyngeal erythema appear alone or in different combinations in the several studies. Rhinorrhea, cough, and conjunctivitis usually appear as symptoms associated with viral infection ( p <0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have been published aiming to elucidate the clinical picture accuracy for the etiological diagnosis of APT in children, with variable results. 7 , 8 , 12 - 15 Rimoin et al 16 demonstrated the existence of significant variation in the clinical presentation of APT in four different countries, suggesting it is inadequate to extrapolate conclusions about the clinical picture accuracy from one region to another. Therefore, the importance of the present study is emphasized, conducted in a country where RF and its complications are a major public health problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation